Israel Among the Nations : International and Comparative Law Perspectives on Israel's 50th Anniversary - Einhorn, Talia,; Kellermann, Alfred E.,; Siehr, Kurt, (International Law - Book Archive pre-2000, 1999)
This book, written on the occasion of Israel's 50th Anniversary, underlines the tension between Israel, the unique Jewish State among nations, and Israel, a nation like many others. On the one hand, it analyzes her special features: the founding of the State, Israel's contributions to the development of the Law of Nations, and her complex relations with the United Nations. On the other hand, it cautions against originality where harmony is required. Citizens can only enjoy their rights and freedoms if constitutionalism and constitutional values are given a firm legal basis. Legislation and jurisprudence must provide them with the certainty and the security needed to acquire rights, conduct their affairs and engage in transactions both domestic and foreign. The experience gained in the European Community and other European States on their road to harmonization could provide helpful guidance.